Inhibiting Interleukin 17 Can Ameliorate the Demyelination Caused by A. cantonensis via iNOS Inhibition - Ying, Feng; Cunjing, Zheng; Feng, Feng; Shuo, Wan; Xin, Zeng; Fukang, Xie; Zhongdao, Wu (Mediators of Inflammation, 2017)
Angiostrongylus cantonensis (A. cantonensis) is an important food-borne parasitic disease. Previous study showed that A. cantonensis infection can cause demyelination in the central nerve system, but the mechanism of action has not been understood. To explore the mechanism and to look for effective therapeutic methods, interleukin 17A (IL-17A) and iNOS expressions were detected during A. cantonensis infection. In addition, IL-17A-neutralizing antibody was applied to treat A. cantonensis-infected mice. In our results, we found that IL-17A and iNOS RNA expressions increased gradually in the process of A. cantonensis infection. When infected mice were treated with IL-17A-neutralizing antibody, the pathologic changes of demyelination alleviated obviously, followed with the elevation of myelin basic protein (MBP) in the brain. In addition, the iNOS expression of the brain in infected animals also showed a decrease in astrocytes. Our study provided evidence that IL-17A may take part in the demyelination caused by A. cantonensis and inhibiting IL-17A expression can ameliorate the pathologic changes of demyelination. Moreover, the decreasing of iNOS expression may be the key reason for the effect of IL-17A inhibition on demyelination caused by A. cantonensis.